ARTIFICIAL INTELLIGENCE (AI) BASED JOURNAL ARTICLE WRITING TRAINING FOR COMPUTER COURSE PARTICIPANTS AT LKP GUNA RAYADI ILMU BANDA ACEH - Abdul Manan; Yusra Jamali; Saddam; Muhammad Yassir; Adnin AS; Evi Mauliza; Muhammad Falik Arsa; Agustizar; Said syaifullah; Saprijal; Riyan Maulana; Rahmat Arfan; Muridha Hasan; Sudarma JA; Deni Trianda Pitri; Lusi Tutur Mulia; Diah Eka Puspita; Sabitah; Roezaini Soefi; Yonoriadi (Jurnal Pengabdian Bangsa, 2026)
The development of Artificial Intelligence ( AI) technology has provided new opportunities in the world of education , especially in supporting scientific writing activities . However , most computer course participants still have limitations in understanding journal article writing techniques that comply with scientific principles and the effective and ethical use of AI. This community service activity aims to improve the competence of computer course participants in writing AI - based journal articles at LKP Guna Rayadi Ilmu Banda Aceh. The method of implementing the activity includes the preparation stage , training implementation , direct practice , mentoring , and evaluation . The participants numbered 25 people from various educational backgrounds . The material provided included an introduction to AI in scientific writing , reference search techniques using Google Scholar, the use of ChatGPT for compiling article outlines , the use of Mendeley in reference management , and the ethics of using AI in academic writing . The results of the activity showed an increase in participants' understanding of the structure of journal articles and the use of AI as a writing aid . Eighty -eight percent of participants were able to draft simple scientific articles in journal format , while 92 % stated that the training was very beneficial in improving their academic skills . This activity demonstrates that the appropriate use of AI can improve the effectiveness and efficiency of the scientific article writing process .